COMPARATIVE ANALYSIS OF MORPHOMETRIC PARAMETERS OF THE LIVER IN PREGNANCY AGAINST THE BACKGROUND OF EXPERIMENTALLY INDUCED CHRONIC KIDNEY DISEASES - Rakhmankulova , N.G. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The treatment of liver diseases that occur against the background of chronic kidney diseases during pregnancy, as well as the prevention of their consequences, remain an urgent medical and social problem worldwide. Despite the progress in the development of methods for the prevention, diagnosis and therapy of liver diseases, the mortality rate remains high. In our country, special emphasis is currently being placed on improving the social protection and healthcare system, as well as improving the quality of diagnosis, treatment and prevention of chronic liver diseases.